A Macrophage-Related Gene Signature for Identifying COPD Based on Bioinformatics and ex vivo Experiments - Zhang Z; Yu H; Wang Q; Ding Y; Wang Z; Zhao S; Bian T (Dove Medical Press, 2023)
Zheming Zhang,1,2,* Haoda Yu,1,2,* Qi Wang,3 Yu Ding,1,2 Ziteng Wang,1,2 Songyun Zhao,1 Tao Bian1,2 1Wuxi Medical Center of Nanjing Medical University, Wuxi, People's Republic of China; 2Department of Respiratory Medicine, Wuxi People's Hospital, Nanjing Medical University, Wuxi, People's Republic of China; 3Department of Gastroenterology, Affiliated Hospital of Jiangsu University, Zhenjiang, People's Republic of China*These authors contributed equally to this workCorrespondence: Tao Bian; Songyun Zhao, Email btaophd@sina.com; 2021122190@stu.njmu.edu.cnBackground: This study aims to investigate the association between immune cells and the development of COPD, while providing a new method for the diagnosis of COPD according to the changes in immune microenvironment.Methods: In this study, the "CIBERSORT" algorithm was used to estimate the tissue infiltration of 22 types of immune cells in GSE20257 and GSE10006. The "limma" package was used for differentially expressed analysis. The key modules associated with vital immune cells were identified using WGCNA. GO and KEGG enrichment analysis revealed the biological functions of the candidate genes. Ultimately, a novel diagnostic prediction model was constructed via machine learning methods and multivariate logistic regression analysis based on GSE20257. Furthermore, we examined the stability of the model on one internal test set (GSE10006), three external test sets (GSE8545, GSE57148 and GSE76925), one single-cell transcriptome dataset (GSE167295), macrophages (THP-M cells) and lung tissue from COPD patients.Results: M0 macrophages (AUC > 0.7 in GSE20257 and GSE10006) were considered as the most important immune cells through exploring the immune microenvironment landscapes in COPD patients and healthy controls. The differentially expressed genes from GSE20257 and GSE10006 were divided into six and five modules via WGCNA, respectively. The green module in GSE20257 (cor = 0.41, P < 0.001) and the brown module in GSE10006 (cor = 0.67, P < 0.001) were highly correlated with M0 macrophages and were selected as key modules. Forty-one intersected genes obtained from two modules were primarily involved in regulation of cytokine production, regulation of innate immune response, specific granule, phagosome, lysosome, ferroptosis, and other biological processes. On the basis of the candidate genetic markers further characterized via the "Boruta" and "LASSO" algorithm for COPD, a diagnostic model comprising CLEC5A, FTL and SLC2A3 was constructed, which could accurately distinguish COPD patients from healthy controls in multiple datasets. GSE20257 as the training set has an AUC of 0.916. The AUCs of the internal test set and three external test sets were 0.873, 0.932, 0.675 and 0.688, respectively. Single-cell sequencing analysis suggested that CLEC5A, FTL and SLC2A3 were expressed in macrophages from COPD patients. The expressions of CLEC5A, FTL and SLC2A3 were up-regulated in THP-M cells and lung tissue from COPD patients.Conclusion: According to the variations of immune microenvironment in COPD patients, we constructed and validated a novel macrophage M0-associated diagnostic model with satisfactory predictive value. CLEC5A, FTL and SLC2A3 are expected to be promising targets of immunotherapy in COPD.Keywords: COPD, CLEC5A, FTL, SLC2A3, immune infiltration, WGCNA, machine learning, multivariate logistic regression